Development of Lathe Attachment for a CNC Machine - Roy V.; Kumar S. (My University, 2025)
A lathe attachment has been developed for an existing CNC machine (installed with rapid prototyping attachment) using conceptual design. The CNC machine operates on mechatronic controls and a computer interface called CAMSOFT, and is used as a CNC Lathe after installing the respective attachment to it. The conceptual design phase, starts from an idea and different components of the lathe are designed as attachment using CAD modelling and is followed by fabrication phase. The lathe attachment is successfully developed and is installed to the CNC machine. The working of the CNC Lathe attachment is checked by making some machining operation like turning and thread cutting. The machining operations are successfully done. The CNC machine becomes multifunctional with the presently developed lathe attachment and the existing RP (rapid prototyping) attachment, and can be used accordingly by installing the respective attachment to it. The CNC machine is useful for carrying research work in both the fields, when installed with the appropriate attachment. © 2013, The Institution of Engineers (India).